BIODETERIORATION OF CHEMICAL CONSTITUENTS IN FRESH AND MARKET ROOTS OF DRUG URARIA PICTA DC. UNDER STORAGE - RASHIDI MASOUMEH; S S DEOKULE (International Journal of Pharma and Bio Sciences, 2013)
In the present investigation the fresh and market roots of drug Uraria picta DC. were selected. Root samples were stored under different 30, 50, 75, 96 and 100 % relative humidity and different incubation days 15, 30, 45 and 60 days. Quantitative estimation of sugars (total sugars, reducing sugar), proteins, phenols and glycosides in fresh and in market condition was done. The results revealed that biodeterioration of selected chemical constituents were observed under high relative humidities 75, 96 and 100% RH and with the length of incubation days 45 and 60 days. More deterioration of chemical constituents recorded in case of market samples as compared to genuine samples. Analysis of variance also showed that the effect of relative humidity and incubation days on biodeterioration of total alkaloid amount were significant.